1987
DOI: 10.1017/s0021859600081818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest methods on the second flush yield of short-duration pigeonpea (Cajanus cajari)

Abstract: Short-duration pigeonpea can give up to three harvests in environments with mild winters (e.g. minimum temperature above 10 °C) such as those prevailing in peninsular India (Sharma, Saxena & Green. 1978; Chauhan, Venkataratnam & Sheldrake, 1984). This is mainly due to the short time (about 120 days) taken to produce the first flush, and the strong perennial character of pigeonpea. The seed yield of short-duration pigeonpea in this multipleharvest system may reach 5'2 t/ha (Chauhan et al. 1984). Venkataratnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Thus, the results of the present study and those of others (Chauhan et al 1987a;Rao & Sachan 1988;Ahmed & Carangal 1989) have confirmed the high ratoon yield potential of short-duration pigeonpea cultivars. In the earlier studies, among the limited number of genotypes tested, ICPL 87 was found to be the best genotype for ratooning (Chauhan et al 19876;Ahmed & Carangal 1989). The results of the present study suggest that several other genotypes may give a higher ratoon yield than ICPL 87.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the results of the present study and those of others (Chauhan et al 1987a;Rao & Sachan 1988;Ahmed & Carangal 1989) have confirmed the high ratoon yield potential of short-duration pigeonpea cultivars. In the earlier studies, among the limited number of genotypes tested, ICPL 87 was found to be the best genotype for ratooning (Chauhan et al 19876;Ahmed & Carangal 1989). The results of the present study suggest that several other genotypes may give a higher ratoon yield than ICPL 87.…”
Section: Discussionmentioning
confidence: 94%